2016
DOI: 10.1038/ajg.2016.122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Running on Gastroesophageal Reflux and Reflux Mechanisms

Abstract: Running induces gastroesophageal reflux almost exclusively through TLESRs. These are not more frequent during exercise but are more often associated with a reflux episode, possibly due to increased abdominal pressure, body movement, a change in esophagogastric junction morphology, and a decreased esophageal clearance during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
3
19
0
3
Order By: Relevance
“…Physical activity may alter TPG due to changes in both AP and TP (20) . Also, the number of TLESR seems to increase during exercise (21) . During the postprandial period, and increase in AP and TPG may be noticed (22) .…”
Section: Transdiaphragmatic Pressure Gradient In Healthmentioning
confidence: 91%
“…Physical activity may alter TPG due to changes in both AP and TP (20) . Also, the number of TLESR seems to increase during exercise (21) . During the postprandial period, and increase in AP and TPG may be noticed (22) .…”
Section: Transdiaphragmatic Pressure Gradient In Healthmentioning
confidence: 91%
“…Central obesity measured by abdominal visceral adipose tissue volume, but not BMI or waist circumference, was associated with EE. Recent studies have suggested that running or abdominal compression as a mechanical factor is correlated with GERD, and results of combined high-resolution pH measurement and manometry should be used (11,18).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of GERD account for most upper gastrointestinal symptoms in healthy athletes and worsen with the intensity of physical activity and during postprandial activity. Especially during high intensity workout [maximal oxygen uptake (VO 2 max) >90%], the number and duration of reflux episodes increase by decreased esophageal motility, decreased pressure of the lower esophageal sphincter ( 22 , 23 ), increased intraabdominal pressure, decreased intestinal blood flow, and body positioning ( 22 , 23 ). Aerobic training improves all of these these mechanisms.…”
Section: Discussionmentioning
confidence: 99%